Influence of Hospitality Careers on Preferred Family Size - Francis, Kabii; Wandaka, John K. M. (Advances in Social Sciences Research Journal, 2023)
The aim of this research was to investigate the influence of hospitality careers on preferred family size. The specific objective was to examine whether ladies' level of education, age, and careers influence their decision on the number of children they would have. The descriptive research method was used in the study. The data was collected from 186 respondents who were randomly selected. The study triangulated both qualitative and quantitative methods. The majority 46% of the respondents had 1 to 2 children while 30% had 3 to 4 children with a minority of 8 % having between 4 to 6 children. This finding was significant X2 =88.377, df (4), p<.0001 It was found that women's employment, education, marital status, attitude toward having children, and availability of family planning methods influenced their family size. There were weak positive correlations (r=0.195) p<0.026) between the hospitality career and the preferred family meaning that the career influenced respondents' attitude towards family size. There was a positive correlation between job flexibility and intention to have a family (r=-.483, p<.003.) There were weak inverse correlations between the financial cost of bringing up children and the number of children a family would like to have (r=-227, p<.012).